Identifying Criteria of Weariness on Urban Areas (Case Study: Samen District of Mashhad) - Babaei, Javad; Rahim Rahnama, Mohammad; Ali Khakpour, Bara’at; Shokouhi, Mohammad (International Journal of Engineering and Technology, 2018)
Today, one of the challenges of modern urbanization in Iran is the issue of old and worn-out urban textures and identification of their criteria. Samen District of Mashhad, a historical texture in an area of 321 hectares, was selected as the study sample. The aim of this study was to determine priorities of improving old neighborhoods based on criteria of weariness. The research adopted a descriptive-analytical method and used the model of Analytical Hierarchy Process (AHP) for the process analysis. The data collection was conducted by a questionnaire (according to Cochranâ€™s formula, 287 questionnaires were randomly distributed in 6 neighborhoods using random sampling method), mapping and field study. Six parameters and twenty four indices were measured as criteria affecting the weariness process. Results showed that physical, constructional, environmental, economic, and social and services parameters had respectively the highest impact on worn-out urban texture. In addition, Eidgah, Payin Khiyaban, Tabarsi, Noghan, Bala Khiyaban and Chaharbagh were ranked first and sixth in terms of the degree of weariness and intervention priorities were specified in each neighborhood.Â